The importance of the focus of the cognitive-behavior therapy related to the body sensation in the panic disorder: case report (Archives of Clinical Psychiatry, 2007)
BACKGROUND: The current cognitive conceptualization for the panic disorder (PD) enhances the fears of body sensations (BS) in consequence of evaluations distorted by the individual who interprets in an erroneous form the BS as catastrophic. OBJECTIVE: The importance of this study is to emphasize the importance of an intensive work of induction of panic symptoms, with cognitive-behavioral therapy (CBT) techniques related to the BS. METHOD: The case of E., woman, 56 year-old, was selected from a research carried through in the Laboratory of Panic and Respiration - IPUB (UFRJ) with a group of patients with PD diagnosis treated with medication and 16 CBT sessions targeted in panic symptoms induction exercises, compared with a control group that used only medication. RESULTS: The results had been controlled through questionnaires and scales applied before and after the interventions. The patient presented hypochondriac symptoms, sensation of shortness of breath, palpitations and fear or loosing control, especially when inside of buses, subways or tunnels. She received a tricycle antidepressant, imipramina, 75 mg/day and 16 CBT sessions. CONCLUSION: At the end of the trial, the patient had panic free status and presented significant improvement of the agoraphobic behavior.